An energy-efficient membrane rotating biological contactor for wastewater treatment - Waqas, S. (Elsevier Ltd, 2021)
Membrane filtration exhibits excellent separation performance for water and wastewater treatment but is still limited by the membrane fouling. This study presents a novel membrane rotating biological contactor (MRBC) that combines a conventional rotating biological contactor (RBC) with membrane filtration. MRBC combines conventional RBC with the membrane filtration placed in between two adjacent rotating disks to offer inherent control over membrane fouling. The disks rotations provide some degree of foulant removal, maintain membrane permeability, and potentially save a substantial amount of energy. The biological and hydraulic performance of MRBC was compared with a series of RBC and external membrane filtration (RBC + ME) where the membrane is treated as a post-treatment unit. Results show that the MRBC enhances not only the biological performance but also offers advantages for inherent membrane fouling control through the rotation of the disk. Membrane fouling control primarily originates from the enhanced shear rate from higher disk rotation and minimum membrane-to-disk gap. The hydraulic performance is 92.4 higher than literature, which further enhanced at smaller membrane-to-disk gaps and higher disk rotations. The highest steady-state permeability of 297 L/(m2.h.bar) and 288 L/(m2.h.bar) results at 40 rpm disk rotational speed and 0.5 cm membrane-to-disk gap, respectively. A projected full-scale MRBC consumes 0.18 kWh/m3 permeate, one-fourth of the energy for the referenced MBR system thanks to the active role of disks rotation for membrane fouling control which eliminates the need of extensive aeration like in the traditional MBRs. MRBC offers a promising alternative for traditional wastewater treatment as a low energy foot-print process, which is in line with the requirements of sustainable development and promotes the development of cleaner production. Â© 2020 Elsevier Ltd